Pediatric abdominal non‐Hodgkin's lymphoma: diagnosis through surgical and non‐surgical procedures - Arthur Almeida Aguiar; Luciana Cavalvanti Lima; Cláudia Corrêa de Araújo; Rodrigo Melo Gallindo (Brazilian Society of Pediatrics, 2019)
Objective: To describe the success rate and the complications after procedures to diagnose abdominal non‐Hodgkin's lymphoma in children and adolescents. Methods: A retrospective cross‐sectional study was conducted with a population consisting of children and adolescents with abdominal non‐Hodgkin's lymphoma diagnosed between September 1994 and December 2012. The sample comprised of 100 patients who underwent 113 diagnostic procedures, including urgent surgery (n = 21), elective surgery (n = 36), and non‐surgical diagnosis (n = 56). Results: The most frequent procedures were laparotomy (46.9%) and ultrasound‐guided core biopsy (25.6%). The rate of diagnostic success was 95.2% for urgent surgeries; 100% for elective surgeries and 82.1% for non‐surgical procedures (p < 0.05). The rates of complication during the three diagnosis procedures considered were significant (p < 0.001; 95.2% of the urgent surgeries, 83.8% of the elective surgeries, and 10.7% of the non‐surgical procedures). The length of time before resuming a full diet and starting chemotherapy was significantly reduced for patients who underwent non‐surgical procedures when compared with the other procedures (p < 0.001). Conclusion: Non‐surgical procedures for the diagnosis of pediatric abdominal non‐Hodgkin's lymphoma are an effective option with low morbidity rate, allowing an earlier resumption of a full diet and chemotherapy initiation. Furthermore, non‐surgical procedures should also be considered for obtaining tumor samples from patients with extensive disease. Resumo: Objetivo: Descrever a taxa de sucesso e as complicações dos procedimentos para o diagnóstico de linfoma não Hodgkin abdominal em crianças e adolescentes. Métodos: Estudo retrospectivo transversal em uma população de crianças e adolescentes com linfoma não Hodgkin abdominal diagnosticada entre setembro de 1994 e dezembro de 2012. A amostra foi composta por 100 pacientes submetidos a 113 procedimentos diagnósticos, inclusive cirurgia de urgência (n = 21), cirurgia eletiva (n = 36) e diagnóstico não cirúrgico (n = 56). Resultados: Os procedimentos mais frequentes foram laparotomia (46,9%) e biópsia guiada por ultrassonografia (25,6%). A taxa de sucesso diagnóstico foi de 95,2% para cirurgias de urgência; 100% para cirurgias eletivas e 82,1% para procedimentos não cirúrgicos (p < 0,05). Houve diferença significativa entre as taxas de complicação associadas aos três grupos (p < 0,001; 95,2% das cirurgias urgentes, 83,8% das cirurgias eletivas e 10,7% dos procedimentos não cirúrgicos). O tempo decorrido até o reinício da dieta plena e o início a quimioterapia foi significativamente reduzido para os pacientes submetidos a procedimentos não cirúrgicos quando comparados com os outros procedimentos (p < 0,001). Conclusão: Os procedimentos não cirúrgicos para o diagnóstico do linfoma não Hodgkin abdominal pediátrico são uma opção efetiva com baixa taxa de morbidade, permitem uma retomada mais precoce de uma dieta plena e início de quimioterapia. Em pacientes com doença extensa, os procedimentos não cirúrgicos também devem ser considerados para a obtenção de amostras tumorais. Keywords: Abdomen, Biopsy, Non‐Hodgkin's lymphoma, Pediatric, Surgery, Palavras‐chave: Abdome, Biópsia, Linfoma não Hodgkin, Pediátrico, Cirurgia